Explaining store behavioral loyalty: the antecedents and roles of store image, self-image, and social and environment image in the fashion industry / Jamaliah Mohd. Yusof, Prof. Madya Dr. Rosidah Musa and Prof. Madya Dr. Sofiah Abd Rahman - Mohd. Yusof, Jamaliah; Musa, Rosidah; Abd Rahman, Sofiah (Research Management Institute (RMI), 2010)
This study was mainly aimed at understanding the perceptions of Malaysian consumers to the image of the store which in turn examined its effect on store loyalty. Self-Congruity theory was employed as a theoretical foundation for developing the present conceptual model. More significantly, this study investigated the symbolic store image and self-image congruence, functional store image and social responsibility image relationships in addition to shopping orientations and past shopping experience as antecedents. Accordingly, the data for this study was collected from sample population of consumers in the Klang Valley using drop-off and collect technique. Shopping behavior of respondent from 565 usable questionnaires was analyzed. Using the item analysis and exploratory factor analysis, the measures were purified and subsequently refined using confirmatory factor analysis from structural equation modeling. Notably, the confirmatory factor analysis ensured measures have met criteria for unidimensionality, validity and reliability. The hypotheses testing for their significant relationship as posited in the conceptual framework were finally examined. Nine of the hypotheses links were supported and one rejected. With some minor modification of the hypotheses links, a plausible model that has a statistical and explanatory power for interpretation of results confidently was established. The findings should provide several key contributions to the marketing and retailing theory as well as retail practitioners. Firstly, it identified atmosphere as the key determinant of functional store image, and legal and ethical aspects as the main influencing factor of social responsibility image. Additionally, actual congruity emerged as the most influential determinant of store image and self-image congruence. Secondly, the findings also suggest that among the three image constructs, functional store image remain as the key determinant of store loyalty while there is no relationship between self-congruity and store loyalty. Nevertheless, the self-congruity relationship with store loyalty was mediated by functional store image and social responsibility image. Interestingly, social responsibility image illuminates its contribution to store loyalty. Notably, shopping orientations and past shopping experience also exhibit a significant positive relationship on image constructs. The findings in this study form part of the strategic recommendations to retailers in the face of competition. Apart from providing empirical results in understanding the Malaysia retail industry, the findings also established an empirical foundation for future research.